Household behavior to manage electricity consumption after the tariff increase - Edward Edward; Johannes Johannes (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The event of price electricity increases in Indonesia since 2017 is expected to encourage households to take planned actions on electricity consumption. Hence, this study is intended to reveal the behavior of households to support electricity consumption saving program of the household consumers. By using the Theory of Planned Behavior approach, it is known that: 1) the respondents realize the importance of saving electricity consumption through their behavior; varied regulating electricity equipment, providing household appliances, the use of electricity saving devices. 2) However, households are hindered by psychological constraints about their uncertainty rewards. 3) There is no evidence that households take planned actions in order to use electricity more economically. Thus, it is recommended that PLN (State Owned Electricity Corporation) continue to carry out integrated communication over household consumer about practices to save electricity. It could be conducted by introducing values established, including rewards that can be adopted by households as part of education to the households.